Pathological lymph node involvement is not a predictor of adverse outcomes in patients undergoing thoracoscopic lobectomy for lung cancer. (29th August 2017) - Abah, Udo; Casali, Gianluca; Batchelor, Timothy James Peacock; Internullo, Eveline; Krishnadas, Rakesh; Joshi, Natasha; Egbulonu, Samson; Warden, Frances; Bruno, Vito Domenico; West, Douglas George
Abstract: OBJECTIVES: As the practice of video-assisted thoracoscopic surgery (VATS) lobectomy gains widespread acceptance, the complexity of procedures attempted increases and the stage of tumour that may be safely approached remains controversial. We examined the impact of nodal involvement with respect to perioperative outcomes after VATS lobectomy. METHODS: All patients listed for VATS lobectomy for non-small-cell lung cancer at our institution from 2012 to 2016 were analysed. Bronchoplastic or chest wall resections and tumours over 7 cm were considered a contraindication to a thoracoscopic approach. RESULTS: Of the 489 patients identified, 97 (19.8%) patients had pathological nodal involvement. The overall conversion rate was 6.1%, reoperation rate was 5.3% and readmission rate was 5.9%. Median hospital stay was 5 days, 30-day mortality was 0.6% and 90-day mortality was 1.6%. No significant difference was identified between the nodal-negative or -positive groups in terms of preoperative demographics, hospital stay, postoperative complications, conversion rate, reoperation rate or readmission rate. Univariate logistic regression identified gender, Thoracoscore, dyspnoea score, performance status, chronic obstructive pulmonary disease, previous stroke, preoperative lung function and non-adenocarcinoma as predictors of postoperative complications. A multivariate model including nodal status identified Thoracoscore (odds ratio 1.57, 95% confidence interval 1.16–2.18; P  < 0.001) and preoperative transfer factor (odds ratio 0.97, 95% confidence interval 0.96–0.98; P  < 0.001) as the only predictors of complications. CONCLUSIONS: In non-small-cell lung cancer patients with pathological hilar or mediastinal lymph node involvement, VATS lobectomy can be safely performed, as there does not appear to be an adverse effect on the incidence of perioperative complications, length of stay or readmissions.